Liberdade, estado e religião nos lineamentos da filosofia do direito de Hegel - Senna, Sabrina Paradizzo (2017)
I intend to analyse the conceptions of Hegel concerning the Freedom and the State, to relate Religion, State and Freedom inside of his thought. We will approach on the question of there recognition in the Phenomenology of Spirit, treating in specific about the relation between Master and Slave, as this recognition it’s just mutual, and soon, as the freedom is capable of objectifying itself in the Ethical, but specificallyin the State in the Elements of the Philosophy of Right. We will demonstrate as to reach the figure of the State, passing for the moments of the Ethical of the Family and the Civil Society, beyond displaying which is the place of the religion in this process of concretization of the freedom, also using the Encyclopaedia of the Philosophical Sciences and Lectures on the Philosophy of Religion. We will see as the freedom, that passing all the hegelian thought, is the objective reach of the State and the Religion. To the end of the chapters, we will still bring critical of Honneth in respect to the Hegel.